2018
DOI: 10.1186/s12920-018-0329-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial sequences in plasma cell-free DNA for early-onset breast cancer patients and healthy females

Abstract: BackgroundCell-free circulating DNA (cfDNA) is becoming a useful biopsy for noninvasive diagnosis of diseases. Microbial sequences in plasma cfDNA may provide important information to improve prognosis and treatment. We have developed a stringent method to identify microbial species via microbial cfDNA in the blood plasma of early-onset breast cancer (EOBC) patients and healthy females. Empirically, microbe-originated sequence reads were identified by mapping non-human PE reads in cfDNA libraries to microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…Our findings suggested a novel role of bacterial eDNA in disease development, and cancer development in particular, consistent with its reported presence in the systemic circulation in association with cancer and other human diseases [20, 82]. Indeed, recent studies have shown that patients with non-infectious early-onset cancer display elevated plasma levels of eDNA from bacteria, particularly Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggested a novel role of bacterial eDNA in disease development, and cancer development in particular, consistent with its reported presence in the systemic circulation in association with cancer and other human diseases [20, 82]. Indeed, recent studies have shown that patients with non-infectious early-onset cancer display elevated plasma levels of eDNA from bacteria, particularly Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 89%
“…Circulating free DNA (cfDNA) is detected in not only patients with cancer but also in healthy individuals . Most of the studies focused on the diagnostic value of cfDNA in early‐stage neoplastic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2 Circulating free DNA (cfDNA) is detected in not only patients with cancer but also in healthy individuals. 3 Most of the studies focused on the diagnostic value of cfDNA in early-stage neoplastic diseases. The plasma levels of cfDNA were significantly higher in patients with breast cancer than in patients with benign tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently emerging evidences demonstrated the presence of highly divergent bacterial-specific DNA in human blood, though their source of origin is still a mystery to be solved[18, 19, 20]. Huang et al reported that blood bacterial biomarkers had prognostic value for early-onset breast cancer patients[21]. Nevertheless, it is not well understood if any correlation exists between blood microbial DNA and disease progressing in other cancers.…”
Section: Introductionmentioning
confidence: 99%